PENGARUH KUALITAS LAPORAN AUDIT DAN CITRA KANTOR AKUNTAN PUBLIK TERHADAP KEPUASAN KLIEN (Studi Pada Perusahaan Go Public yang Memiliki Kantor Cabang Di Kota Palembang) - Fatma Khairani; Tertiarto Wahyudi; Ahmad Subeki (AKUNTABILITAS, 2017)
This research aims to determine the effect of quality audit reports and public accountant company image for client satisfaction (company goes public) in 2016 which has a branch office in the Palembang city. The sample of this research in 20 clients of public accountant company (companies go public). This research method uses quantitative approach and multiple linear regression analysis data with SPSS version 23,00. The result showed that partially the quality of audit report influence significantly for the client satisfaction (companies go public) in 2016 which has a branch office in the Palembang City., but the image of the public accountant company doesn’t significantly affect the client satisfaction (companies go public) in 2016 which has a branch office in the Palembang city. And simultaneously, the quality of audit reports and the image of public accountant company significantly influence the client satisfaction (company go public) in 2016 which has a branch office in the Palembang city.